2020
DOI: 10.3390/molecules25153552
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Cataluminescence Sensor Based on Nanosized V2O5 for 2-Butanone Detection

Abstract: The development of high-performance sensors is of great significance for the control of the volatile organic compounds (VOCs) pollution and their potential hazard. In this paper, high crystalline V2O5 nanoparticles were successfully synthesized by a simple hydrothermal method. The structure and morphology of the prepared nanoparticles were characterized by TEM and XRD, and the cataluminescence (CTL) sensing performance was also investigated. Experiments found that the as-prepared V2O5 not only shows sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…X-ray analysis confirmed that all peaks correspond to the V 2 O 5 orthorhombic phase. The results are well agreed with those obtained by Zhang et al[4], Fu et al ]13] and Schneider[16]. The diffraction peaks of the samples manifest that the samples were well crystallized and correspond to the JCPDS Card numbering 41-1426.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…X-ray analysis confirmed that all peaks correspond to the V 2 O 5 orthorhombic phase. The results are well agreed with those obtained by Zhang et al[4], Fu et al ]13] and Schneider[16]. The diffraction peaks of the samples manifest that the samples were well crystallized and correspond to the JCPDS Card numbering 41-1426.…”
supporting
confidence: 91%
“…The gas sensing procedure is generally relevant to the surface adsorption and surface interaction of gas molecules on the metal oxide nanoparticle. The operating temperature acts a crucial part in gas detection and has a chief effect to determine the kind of chemisorbed oxygen species [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CTL, a kind of chemiluminescence (CL) emitted from heterogeneous catalytic oxidation reactions on the gas–solid interface, has been considered as a promising energy transduction mechanism for fabricating gas sensors . In recent years, a series of CTL sensing applications have been attempted to develop for diethyl ether and many other molecules at different laboratories. However, a higher working temperature above 200 °C is not conducive to the stability of the sensor signal …”
Section: Introductionmentioning
confidence: 99%